Usability and ease of use of long-term remote monitoring of physical activity for individuals with acquired brain injury in community: a qualitative analysis - Mazzeo, Marie; Hernan, Gabriel; Veerubhotla, Akhila (Frontiers in Neuroscience, 2023)
Objective and continuous monitoring of physical activity over long-term in the community is perhaps the most important step in the paradigm shift towards evidence-based practice and personalized therapy for successful community integration. With the advancement in technology, physical activity monitors have become the go-to tools for objective and continuous monitoring of everyday physical activity in the community. While these devices are widely used in many patient populations, their use in individuals with acquired brain injury is slowly gaining traction now. The first step before using activity monitors in this population is to understand the patient perspective on usability and ease of use of physical activity monitors at different wear-locations. However, there are no studies that have looked at the feasibility and patient perspectives on long term utilization of activity monitors in individuals with acquired brain injury. This pilot study aims to fill this gap and understand patient reported aspects of feasibility of using physical activity monitors for long term use in community dwelling individuals with acquired brain injury. This pilot study found that patients with acquired brain injury faced challenges specific to their functional limitations and the activity monitors worn on waist or wrist may be best suited in this population.